Development of Educational Tutorial Videos Through Tiktok on Double Cleansing Facial Treatments - Fadhilah, Intan; Arum, Aniesa Puspa; Hidayah, Nurul (Journal of English Language and Education, 2025)
In its development, social media now plays an important role in supporting the dissemination of educational content, especially in the realm of non-formal learning that is easily accessible with the lifestyle of people in today's modern era. Various social media platforms such as TikTok, Instagram, and YouTube have evolved from what were initially just places to share entertainment content to means of disseminating educational information. This study aims to develop educational tutorial videos on double cleansing facial care through the TikTok platform, which can be used as an additional learning resource for social media users based on evaluations by subject matter experts and media experts. This study employs the Research Development (RD) method using the ADDIE development model, which includes five phases: Analysis, Design, Development, Implementation, and Evaluation. The measurement tools used in this study include validation tools by media experts and users, as well as practical feasibility testing tools by media experts. The results of the study show that the educational videos produced received very high validation in terms of both content and media. The performance of the videos on the TikTok platform also supports the effectiveness of this media in reaching digital audiences. The output of this research is an educational tutorial video that can be accessed online anytime and anywhere, thereby supporting self-directed learning and enhancing digital literacy in the context of self-care.